Lipopolysaccharide (LPS) Inner-Core Phosphates Are Required for Complete LPS Synthesis and Transport to the Outer Membrane in Pseudomonas aeruginosa PAO1 - DeLucia, Angela M. (American Society of Microbiology, 2011)
Gram-negative outer membrane (OM) integrity is maintained in part by Mg(2+) cross-links between phosphates on lipid A and on core sugars of adjacent lipopolysaccharide (LPS) molecules. In contrast to other Gram-negative bacteria, waaP, encoding an inner-core kinase, could not be inactivated in Pseudomonas aeruginosa. To examine this further, expression of the kinases WaaP or WapP/WapQ/PA5006 was placed under the control of the arabinose-regulated pBAD promoter. Growth of these strains was arabinose dependent, confirming that core phosphorylation is essential in P. aeruginosa. Transmission electron micrographs of kinase-depleted cells revealed marked invaginations of the inner membrane. SDS-PAGE of total LPS from WaaP-depleted cells showed accumulation of a fast-migrating band. Mass spectrometry (MS) analysis revealed that LPS from these cells exhibits a unique truncated core consisting of two 3-deoxy-d-manno-octulosonic acids (Kdo), two l-glycero-d-manno-heptoses (Hep), and one hexose but completely devoid of phosphates, indicating that phosphorylation by WaaP is necessary for subsequent core phosphorylations. MS analysis of lipid A from WaaP-depleted cells revealed extensive 4-amino-4-deoxy-l-arabinose modification. OM prepared from these cells by Sarkosyl extraction of total membranes or by sucrose density gradient centrifugation lacked truncated LPS. Instead, truncated LPS was detected in the inner membrane fractions, consistent with impaired transport/assembly of this species into the OM.